“All Israel has a Portion in the World to Come”: Attempts to Create a Coherent Narrative of Reward and Punishment in Medieval Jewish Philosophy - Kreisel, Howard (Jewish Thought, 2023)
Various notions pertaining to future reward and punishment are mentioned in biblical and rabbinic literature – e.g., the messianic era, the World to Come, the resurrection of the dead, the Garden of Eden, Gehinom – but no attempt was ever made to create a coherent narrative from these different notions. It was left to the medieval Jewish thinkers to fill this void, basing themselves on the sources of Jewish tradition and their own philosophical views. In this article, I explore the approaches of four medieval philosophers: Saadiah Gaon, Joseph Ibn Ẓaddik, Maimonides (1138–1204), and Ḥasdai Crescas. My primary focus will be the ultimate fate of the individual. The issue of naturalism vs. supernaturalism remains a central one in my treatment of this subject – that is to say, how God’s governance of the world is to be conceived. At the same time, I will take a closer look at another major issue that has not been sufficiently emphasized in previous studies; namely, how these thinkers conceived of the nature of the individual in their approaches to one’s final state. In other words, how did they think of the “I,” whether in this world or the next? Their various approaches to this problem find their clearest expression in the attempts to understand the nature of the World to Come and how the cardinal rabbinic belief in the resurrection of the dead fits into the story of ultimate reward. As I will try to show, more often than not one can detect a dissonance in their approaches due to their conflicting religious and philosophical commitments, particularly due to the strong body/soul dichotomy that infiltrated medieval Jewish thought from Greek thought.